Essential Hypertension and Variations in Renal Volume in a Population of Punjab - Shahzad Shokat, Nouman Hameed, Muhammad Omer, Muhammad Aamer, Mufassar Nishat, Sultan Sikandar (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: In order to establish a correlation between this parameter and demographic characteristics such as age, gender, body mass index (BMI), body surface area (BSA), and length of hypertension treatment, it is necessary to measure the renal volume of adult patients who are suffering from essential hypertension. Methods: Sonography was used to examine a total of 46 people who were participants in this prospective trial. All of these people had essential hypertension and normal renal function. Within the population of patients, there were a total of 46 people: 23 males and 23 females. In addition, as a control group, we analysed the blood pressure levels of normal adults (sixty males and sixty females) who did not have hypertension. After that, the renal volume was calculated by applying the formula LWAP0.523, which was derived from the length, breadth, and anterio-posterior diameter of the kidney. The results of this calculation were then presented. Results: According to the findings, the range of renal volume that was obtained was 49.52414+0.01 cm3, with a mean of 109.14231+32 cm3 for the left kidney. Meanwhile, the range of renal volume that was acquired for the right kidney was 42.44266+.61 cm3, with a mean of 101.23547+.23 cm3. Males had significantly greater right and left kidney volumes overall compared to females, who had smaller kidney volumes overall. In men, the volume of the right kidney was determined to be 101.4231+.56 cm3, whereas the volume of the left kidney was determined to be 114.2675+.23 cm3 (97.4545+.04 cm3 and 99.7414+.57 cm3, respectively). Although there was a significant relationship between the renal volume and both the body mass index and the body surface area, renal volume decreased with increasing age. There was no correlation found between the amount of urine produced by the kidneys and the length of time the individual had hypertension. Conclusion: Patients suffering from hypertension, regardless of gender, have a higher amount of fluid in their left kidney compared to their right kidney. In addition, the size of the kidneys in patients who have hypertension and are female is smaller than the size of the kidneys in patients who have hypertension and are male. The researchers discovered a correlation between renal volume, body surface area, and body mass index. In addition, it has been demonstrated that the volume of both kidneys decreases with increasing age. On the other hand, there is no correlation between the size of the kidneys and the duration that hypertension continues to exist in a person’s body. keywords: Essential hypertension, renal volume, ultrasonography